DIAGNOSIS EFEKTIVITAS ORGANISASI MODEL 7S MCKINSEY - Dian Komarsyah Djuardi; Hani Damayanti Aprilia; Nur Efendi; Deddy Aprilani (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2019)
The aim of this research is seeking further on organization’s effectivity through 7S McKinsey in FISIP Universitas Lampung using qualitative method. We found that the seven dimensions (strategies, system, staff, skills, structures, and style) have been established in the organization. The six dimensions give potentially positive influence in the working goals, only one which is staff that have negative influence.